Streptococcus pneumoniae acquisition among vaccinated Malaysian hajj pilgrims and its associated factors - Aniza, Abd Aziz; Nabilah, Ismail; Nur Adlina, Zainuddin (2017)
Objective: To describe the acquisition of Streptococcus pneumoniae among Malaysian hajj pilgrims and to determine the association with pneumococcal vaccination and respiratory symptoms. Methods: This was a cross sectional study performed on Malaysian hajj pilgrims in a mass ritual gathering event from October to November 2013 in Makkah. Demographic data and associated factors for the respiratory infection were obtained by interview at Kota Bharu airport on their return. A sputum specimen or throat swab was taken from all subjects for S. pneumoniae culture and antimicrobial susceptibility testing. Results: S. pneumoniae was isolated in 1.81% (n=10, 95% CI 0.69, 2.93) out of 549 subjects. Fifty percent of them (n=5) had received pneumococcal vaccination. Difficulty in breathing was significantly reduced in subjects without S. pneumoniae isolation (p =0.042). In multivariable analysis, the uptake of pneumococcal vaccination was found to be statistically significant in reducing S. pneumoniae acquisition (p =0.018) and those at a younger age were more liable to acquire colonization or infection (p=0.018). Runny nose was significantly associated with the vaccinated group (p=0.040). Conclusion: The acquisition of S. pneumoniae among Malaysian hajj pilgrims in 2013 was significantly low with the uptake of pneumococcal vaccination. J Microbiol Infect Dis 2017; 7(2):56-62